The shield and the cloak the security of the commons - Hart, Gary, 1936- (Oxford : Oxford University Press, 2006)
Hart outlines, in clear, simple prose, the fundamental changes with which America must grapple when confronting a terrorist threat that has no state and no geographic homebase and thus offers no genuine target for the world's largest and most sophisticated military force.
Includes bibliographical references and index.
Description based on print version record.
Keywords: National security -- United States; World politics -- 21st century; United States -- Military policy; United States -- Foreign relations -- 2001-2009.; United States -- Politics and government -- 2001-2009.